Design, synthesis, and biological evaluation of anti-EV71 agents. Issue 14 (15th July 2016) - Li, Peng; Yang, Bailing; Hao, Fei; Wang, Ping; He, Haiying; Huang, Lei; Zhang, Xuan; Zhang, Shengbin; Peng, Xuanjia; Yin, Ke; Hu, Jiao; Chen, Xinsheng; et al.
Graphical abstract: Enterovirus 71 (EV71) is a major causative agent of hand, foot and mouth disease (HFMD), which can spread its infections to the central nervous and other systems with severe consequences. In this article, design, chemical synthesis, and biological evaluation of various anti-EV71 agents which incorporate Michael acceptors are described. Further SAR study demonstrated that lactone type of Michael acceptor provided a new lead of anti-EV71 drug candidates with high anti-EV71 activity in cell-based assay and enhanced mouse plasma stability. One of the most potent compounds (2K, cell-based anti-EV71 EC50 = 0.028 μM), showed acceptable stability profile towards mouse plasma, which resulted into promising pharmacokinetics in mouse via IP administration. Abstract: Enterovirus 71 (EV71) is a major causative agent of hand, foot and mouth disease (HFMD), which can spread its infections to the central nervous and other systems with severe consequences. In this article, design, chemical synthesis, and biological evaluation of various anti-EV71 agents which incorporate Michael acceptors are described. Further SAR study demonstrated that lactone type of Michael acceptor provided a new lead of anti-EV71 drug candidates with high anti-EV71 activity in cell-based assay and enhanced mouse plasma stability. One of the most potent compounds (2K, cell-based anti-EV71 EC50 = 0.028 μM), showed acceptable stability profile towards mouse plasma, which resulted into promising pharmacokinetics in mouse via IP administration.